Solution and Hyers-Ulam-Rassias Stability of Generalized Mixed Type Additive-Quadratic Functional Equations in Fuzzy Banach Spaces - M. Eshaghi Gordji; H. Azadi Kenary; H. Rezaei; Y. W. Lee; G. H. Kim (Abstract and Applied Analysis)
By using fixed point methods and direct method, we establish the generalized Hyers-Ulam stability of the following additive-quadratic functional equation f(x+ky)+f(x−ky)=f(x+y)+f(x−y)+(2(k+1)/k)f(ky)−2(k+1)f(y) for fixed integers k with k≠0,±1 in fuzzy Banach spaces.